x+7=3(2x-1)

Simple and best practice solution for x+7=3(2x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+7=3(2x-1) equation:


Simplifying
x + 7 = 3(2x + -1)

Reorder the terms:
7 + x = 3(2x + -1)

Reorder the terms:
7 + x = 3(-1 + 2x)
7 + x = (-1 * 3 + 2x * 3)
7 + x = (-3 + 6x)

Solving
7 + x = -3 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
7 + x + -6x = -3 + 6x + -6x

Combine like terms: x + -6x = -5x
7 + -5x = -3 + 6x + -6x

Combine like terms: 6x + -6x = 0
7 + -5x = -3 + 0
7 + -5x = -3

Add '-7' to each side of the equation.
7 + -7 + -5x = -3 + -7

Combine like terms: 7 + -7 = 0
0 + -5x = -3 + -7
-5x = -3 + -7

Combine like terms: -3 + -7 = -10
-5x = -10

Divide each side by '-5'.
x = 2

Simplifying
x = 2

See similar equations:

| 4x+3=7x-1.5 | | 6-3p=1 | | 63/3x=21 | | -1x+3x=-3+17x | | 4x+x=3x+1 | | AB+BC=BCD | | 180n^2-360n-2160=0 | | y=0.13+0.4*100 | | 16x-6=16x-6 | | 2x^2+4y^2-2z^2-5y=0 | | Cot(-t)/csc(-t)=cos(t) | | x+2y-3z=-5 | | 6x-1+5y=0 | | 42-(4b/12)=30 | | 6-2(3n+1)=40 | | (W-4/9)(-2/3)=-4-4 | | P=2(200)+2x | | 2x^2+4y^2-2x^2-5y=0 | | -4(2x-5)=44 | | 5p+13-10p=-7 | | 6w+3y+10x+4x-11y+4w= | | 25/4(2/30 | | 2x/3=28 | | 4(c+2)-10=46 | | 25/4(x-2/3)=75/3 | | 6x+2=66-2 | | 2x/23=28 | | 2/9n=n-7 | | 5x+19=3-3x | | 2(y+3)+10=32 | | 2x+21=5x-12 | | (4a+2y)-(4a-3y)= |

Equations solver categories